2018
DOI: 10.1128/aac.01607-17
|View full text |Cite
|
Sign up to set email alerts
|

Peptidoglycan Cross-Linking Activity of l , d -Transpeptidases from Clostridium difficile and Inactivation of These Enzymes by β-Lactams

Abstract: difficile-associated diseases. 52The structure of cell wall peptidoglycan is unusual in C. difficile since the majority

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 24 publications
4
43
1
Order By: Relevance
“…(Peltier et al ., ) and Sutterlin et al . (Sutterlin et al ., ) identified and purified three L,D‐transpeptidases, CD630_29630 (Ldt Cd1 ), CD630_27130 (Ldt Cd2 ) and CD630_30070 (Ldt Cd3 ), in C. difficile 630. Among them, Ldt Cd2 and Ldt Cd3 can catalyse the formation of 3 → 3 cross‐links (L,D‐transpeptidase activity), while Ldt Cd1 displays only L,D‐carboxypeptidase activity (Sutterlin et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…(Peltier et al ., ) and Sutterlin et al . (Sutterlin et al ., ) identified and purified three L,D‐transpeptidases, CD630_29630 (Ldt Cd1 ), CD630_27130 (Ldt Cd2 ) and CD630_30070 (Ldt Cd3 ), in C. difficile 630. Among them, Ldt Cd2 and Ldt Cd3 can catalyse the formation of 3 → 3 cross‐links (L,D‐transpeptidase activity), while Ldt Cd1 displays only L,D‐carboxypeptidase activity (Sutterlin et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…(Sutterlin et al ., ) identified and purified three L,D‐transpeptidases, CD630_29630 (Ldt Cd1 ), CD630_27130 (Ldt Cd2 ) and CD630_30070 (Ldt Cd3 ), in C. difficile 630. Among them, Ldt Cd2 and Ldt Cd3 can catalyse the formation of 3 → 3 cross‐links (L,D‐transpeptidase activity), while Ldt Cd1 displays only L,D‐carboxypeptidase activity (Sutterlin et al ., ). They demonstrated that the inactivation of the ldt Cd1 , ldt Cd2 and ldt Cd1 plus ldt Cd2 could result in a 22%, 15% and 28% decrease in the proportion of muropeptide dimers containing 3 → 3 cross‐links respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations